Holocene Vegetation and Climate inferences from Phytoliths and Pollen from Lagoa do Macuco, North Coast of Espírito Santo State (Brazil) - Calegari, Marcia Regina; Madella, Marco; Buso Jr, Antonio Alvaro; Osterrieth, Margaritha L; Lorente, Flávio Lima; Pessenda, Luiz Carlos R. (Quaternary and Environmental Geosciences, 2015)
An interproxy approach focused on phytoliths and pollen, including radiocarbon dating and sediment particle-size analyses, has been carried out at Lagoa do Macuco, Linhares municipality, Espírito Santo State, Brazil. Three pollen zones were identified: the first one (MAC-C I) indicates the presence of mangrove vegetation between 7700 cal yr BP and 4396 cal yr BP; the second one a displacement of the vegetation from the lower areas to the more elevated margins of the valley (MAC-C II, from between 4396 to 1287 cal. yr BP) and third one (MAC-C III), representing the period of the current lake evolution, between 1287 cal. yr BP and the present day. The displacement of the mangrove seems to be connected to the landward migration of the palaeo-estuary and the flooding of the lower parts of the valley, reflecting the relative sea-level highstand, which occurred after 7000 cal yr BP. The phytolith analysis indicated four main zone. The phytolith zone I (7700-7100 cal yr BP) did not show the presence of phytoliths. The phytoliths zone II (7100-3400 cal yr BP) indicates the presence of an open vegetation predominantly of grasses while phytolith zone III (3400-400 cal yr BP) shows a phase with more forested vegetation. Finally, the phytolith zone IV (400 cal yr BP to modern) has a decrease in tree cover and the setting of vegetation with a strong grasses component. Phytoliths indices indicate trends of humidity and temperature at a more local scale, allowing understanding the environmental conditions during the formation of the current lake.